86.6k views
3 votes
Please help me jog my memory in how to solve a system of equations with the example below

2x + y=4
x - y=-1​

1 Answer

2 votes

Answer:

(1, 2 )

Explanation:

Giving the 2 equations

2x + y = 4 → (1)

x - y = - 1 → (2)

Adding the 2 equations term by term, eliminates the term in y

3x = 3 ( divide both sides by 3 )

x = 1

Substitute x = 1 into either of the 2 equations for corresponding value of y

Substituting x = 1 into (1)

(2 × 1) + y = 4

2 + y = 4 ( subtract 2 from both sides )

y = 2

Solution is (1, 2 )

User Khawar Raza
by
5.3k points